(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article provides an overview of the language code. The role of the language code in intercultural communication is discussed. A classification of the code problem is given. The linguistic nature of second-level signs, their systematicity and conditionality are noted.